2019
DOI: 10.1021/acs.jpca.9b07781
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of Pentafluorophenol: Kinetics and Mechanism of the Reactions of Cl Atoms and OH Radicals

Abstract: Fourier transform infrared smog chamber techniques were used to study the kinetics and mechanisms of the reactions of Cl atoms and OH radicals with pentafluorophenol (C6F5OH) in 700 Torr total pressure of air or N2 diluent at 296 ± 2 K. Rate constants k(OH + C6F5OH) = (6.88 ± 1.37) × 10–12 cm3 molecule–1 s–1 and k(Cl + C6F5OH) = (2.52 ± 0.31) × 10–11 cm3 s–1 molecule–1 in 700 Torr air diluent were determined. In 700 Torr N2, the rate constant for the reaction of C6F5OH with Cl atoms is linearly dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Similar negative temperature-dependent results from a negative activation energy were observed in the reaction of tris(2-chloroisopropyl) phosphate with ˙OH radical. 55 Table S2 (ESI†) shows that the overall rate constant for the ˙OH + C 6 H 5 OH reaction calculated at the CCSD(T)/aug-cc-pVDZ//M06-2X/6-311G(d,p) level was 6.03 × 10 −12 cm 3 molecule −1 s −1 at 296 K, perfectly matching the (6.88 ± 1.37) × 10 −12 cm 3 molecule −1 s −1 deduced by Hasager et al 44 Our results further confirmed that the adopted level was reliable for computing the title reactions, and the calculated results were credible. Tables S3 and S4 (ESI†) show that the rate constants of ˙OH + C 6 Cl 5 OH and ˙OH + C 6 Br 5 OH were 6.27 × 10 −12 and 6.99 × 10 −12 cm 3 molecule −1 s −1 at 296 K. Thus, the rate constant of the substitution of bromine atoms at room temperature was the largest one among the three species, similar to the results of acyl halides.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar negative temperature-dependent results from a negative activation energy were observed in the reaction of tris(2-chloroisopropyl) phosphate with ˙OH radical. 55 Table S2 (ESI†) shows that the overall rate constant for the ˙OH + C 6 H 5 OH reaction calculated at the CCSD(T)/aug-cc-pVDZ//M06-2X/6-311G(d,p) level was 6.03 × 10 −12 cm 3 molecule −1 s −1 at 296 K, perfectly matching the (6.88 ± 1.37) × 10 −12 cm 3 molecule −1 s −1 deduced by Hasager et al 44 Our results further confirmed that the adopted level was reliable for computing the title reactions, and the calculated results were credible. Tables S3 and S4 (ESI†) show that the rate constants of ˙OH + C 6 Cl 5 OH and ˙OH + C 6 Br 5 OH were 6.27 × 10 −12 and 6.99 × 10 −12 cm 3 molecule −1 s −1 at 296 K. Thus, the rate constant of the substitution of bromine atoms at room temperature was the largest one among the three species, similar to the results of acyl halides.…”
Section: Resultssupporting
confidence: 86%
“…In the photocatalytic degradation of pollutants, OH is the most important reactive species, significantly promoting the photocatalytic oxidation efficiencies of gaseous pollutants. 42,43 In experiments, the initial rate constant at room temperature of the OH-radical induced homogeneous degradation of C 6 X 5 OH (X = F, Cl, Br) has been reported by Hasager et al 44 and Fang et al, 45 which has verified the important role of OH radicals in their environmental removal. Nevertheless, the experimental inference still requires theoretical support because the produced highly active intermediates and transition states have short lifetimes, and they are almost impossible to be represented in an experiment.…”
Section: Introductionmentioning
confidence: 73%
“…where [OH] is the $OH concentration, which is 1 Â 10 6 molecule cm −3 in the atmospheric troposphere, 45 and k tot is 7.86 Â 10 −10 cm 3 per molecule per s at 298 K obtained in this work. The lifetime is calculated to be 0.35 h at 298 K, implying that acephate is quickly oxidized by OH radicals in the atmosphere.…”
Section: Reactions Of Oh Radicals and Acephate In Watermentioning
confidence: 81%
“…Furthermore, in order to reveal the ·OH initiated degradation of acephate in the atmosphere, the lifetime ( τ ) was calculated to estimate the reaction time in the atmosphere with the following formula:where [OH] is the ·OH concentration, which is 1 × 10 6 molecule cm −3 in the atmospheric troposphere, 45 and k tot is 7.86 × 10 −10 cm 3 per molecule per s at 298 K obtained in this work. The lifetime is calculated to be 0.35 h at 298 K, implying that acephate is quickly oxidized by OH radicals in the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we aim to gain a fundamental understanding of the interaction between magnesium salt molecules and free radicals since the latter are known to play a crucial role in chemistry, especially organic chemistry, 39,40 atmospheric chemistry 41,42 and biochemistry. 43,44 By using quantum chemical calculations, the formation of single-electron magnesium bond between MgX 2 (X ¼ F, H) and a series of alkyl radicals (methyl, ethyl, isopropyl, and tertiary butyl) was characterized in detail and compared with other noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%